C=C π Bond Modified Graphitic Carbon Nitride Films for Enhanced Photoelectrochemical Cell Performance. Issue 9 (7th April 2017) - Bian, Juncao; Xi, Lifei; Li, Jianfu; Xiong, Ze; Huang, Chao; Lange, Kathrin M.; Tang, Jinyao; Shalom, Menny; Zhang, Rui‐Qin
Abstract: Applications of graphitic carbon nitride (g‐CN) in photoelectrochemical and optoelectronic devices are still hindered due to the difficulties in synthesis of g‐CN films with tunable chemical, physical and catalytic properties. Herein we present a general method to alter the electronic and photoelectrochemical properties of g‐CN films by annealing. We found that N atoms can be removed from the g‐CN networks after annealing treatment. Assisted by theoretical calculations, we confirm that upon appropriate N removal, the adjacent C atoms will form new C=C π bonds. Detailed calculations demonstrate that the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) are located at the structure unit with C=C π bonds and the electrons are more delocalized. Valence band X‐ray photoelectron spectroscopy spectra together with optical absorption spectra unveil that the structure changes result in the alteration of the g‐CN energy levels and position of band edges. Our results show that the photocurrent density of the annealed g‐CN film is doubled compared with the pristine one, thanks to the better charge separation and transport within the film induced by the new C=C π bonds. An ultrathin TiO2 film (2.2 nm) is further deposited on the g‐CN film as stabilizer and the photocurrent density is kept at 0.05 mA cm −2 at 1.23 V versus reversible hydrogen electrode after two‐cycle stability assessment. This work enables the applications of g‐CN films in many electronic and optoelectronic devices. Abstract : Caught on film : C=C π‐bond modifications of graphitic carbon nitride (g‐CN) film have been achieved by annealing, which makes the electrons more delocalized and alters the position of the band edges of g‐CN. The charge carrier transport and separation are thus improved, rendering a doubled photocurrent density as compared to the pristine film.